Responding to clinicians who fail to follow patient safety practices: Perceptions of physicians, nurses, trainees, and patients. Issue 2 (17th December 2013) - Driver, Todd H.; Katz, Patricia P.; Trupin, Laura; Wachter, Robert M.
<x xml:space="preserve">Abstract</x> BACKGROUND The field of patient safety grapples with the tension between a "no‐blame" systems approach and the need to hold providers accountable for substandard performance. Attitudes of clinicians and patients regarding methods of promoting adherence to safety practices have not been described. METHODS We surveyed attending and resident physicians in the University of California, San Francisco (UCSF) Department of Medicine, nurses and inpatients at the UCSF Medical Center, and UCSF medical students regarding attitudes toward violations of 3 safety protocols: hand hygiene, fall risk assessment, and preoperative time‐out. RESULTS Responses to protocol lapses were grouped into 3 categories: feedback (universally endorsed and thus excluded from the analysis), public reporting, and penalty (fines, suspension, firing). We examined group differences regarding whether public reporting and penalties were ever appropriate and the number of transgressions at which public reporting and penalties were favored. Respondents favored both public reporting and penalties more frequently for not conducting a preoperative time‐out or fall risk assessment than for hand‐hygiene lapses (public reporting: time‐out, odds ratio [OR]: 2.82 [95% confidence interval CI: 2.03‐3.91]; fall, OR: 1.47 [95% CI: 1.09‐1.98]. Penalty: time‐out, OR: 4.29 [95% CI: 2.97‐6.20]; fall, OR: 1.74 [95% CI: 1.27‐2.37]). Penalties were endorsed more frequently than public reporting for all groups and scenarios. Attending physicians and patients expressed similar attitudes regarding public reporting and penalties, but patients favored penalties after significantly fewer transgressions (P < 0.05). CONCLUSION After a decade emphasizing no‐blame responses to patient safety hazards, both healthcare providers and patients now believe clinicians should be held accountable for following basic safety protocols. Journal of Hospital Medicine 2014;9:99–105. © 2013 Society of Hospital Medicine